Introgression of a rare haplotype from Southeastern Africa to breed California blackeyes with larger seeds - Lucas, Mitchell R.; Huynh, Bao-Lam; Roberts, Philip A.; Close, Timothy J. (Frontiers in Plant Science, 2015)
Seed size distinguishes most crops from their wild relatives and is an important quality trait for the grain legume cowpea. In order to breed cowpea varieties with larger seeds we introgressed a rare haplotype associated with large seeds at the Css-1 locus from an African buff seed type cultivar, IT82E-18 (18.5g/100 seeds), into a blackeye seed type cultivar, CB27 (22g/100 seed). Four RILs derived from these two parents were chosen for marker-assisted breeding based on SNP genotyping with a goal of stacking large seed haplotypes into a CB27 background. Foreground and background selection were performed during two cycles of backcrossing based on genome-wide SNP markers. The average seed size of introgression lines homozygous for haplotypes associated with large seeds was 28.7g/100 seed and 24.8g/100 seed for cycles 1 and 2, respectively. One cycle 1 introgression line with desirable seed quality was selfed for two generations to make families with very large seeds (28-35g/100 seeds). Field-based performance trials helped identify breeding lines that not only have large seeds but are also desirable in terms of yield, maturity, and plant architecture when compared to industry standards. A principal component analysis was used to explore the relationships between the parents relative to a core set of landraces and improved varieties based on high-density SNP data. The geographic distribution of haplotypes at the Css-1 locus suggest the haplotype associated with large seeds is unique to accessions collected from Southeastern Africa. Therefore this QTL has a strong potential to develop larger seeded varieties for other growing regions which is demonstrated in this work using a California pedigree.